2015
DOI: 10.1016/j.oceaneng.2015.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of innovative developments to the installation process for an offshore wind farm

Abstract: For offshore wind to be competitive with mature energy industries, cost efficiencies must be improved throughout the lifetime of an offshore wind farm (OWF). With expensive equipment hire spanning several years, installation is an area where large savings can potentially be made. Installation operations are subject to uncertain weather conditions, with more extreme conditions as OWF developments tend towards larger sites, further offshore in deeper waters. One approach to reduce the cost of the installation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In order to address the challenges of larger installation projects and increasing uncertainties, two models have been developed in a collaborative project between industry experts and academics to support logistical decision making at the planning or bidding stage of an OWF installation. These models have been presented previously by the authors (Barlow et al (2014c(Barlow et al ( , 2015; Tezcaner Öztürk et al (2016)). Action research (Lewin, 1946) was the chosen methodology to ensure the models developed were grounded in the challenges facing the OWF developers.…”
Section: Introductionmentioning
confidence: 91%
“…In order to address the challenges of larger installation projects and increasing uncertainties, two models have been developed in a collaborative project between industry experts and academics to support logistical decision making at the planning or bidding stage of an OWF installation. These models have been presented previously by the authors (Barlow et al (2014c(Barlow et al ( , 2015; Tezcaner Öztürk et al (2016)). Action research (Lewin, 1946) was the chosen methodology to ensure the models developed were grounded in the challenges facing the OWF developers.…”
Section: Introductionmentioning
confidence: 91%
“…installing separate blades instead of one assembled rotor, a decrease in the installation duration may be made by up to 30 % (Barlow et al, 2015). Another study done by Dowell et al (2013) also showed a significant decrease in delay for lifting operations with higher wind restrictions.…”
Section: Weather Restrictionsmentioning
confidence: 97%
“…Research done by Barlow et al (2015) demonstrate through a simulation model that weather window utilization has high impact on logistical operation durations. Vessel development focusing on improving vessel capacity for carrying components is suggested through simulation to have little impact on operation duration reductions.…”
Section: Weather Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it might be not able to represent the true probabilistic range of weather conditions of a given year. The method used by (Barlow et al, 2015) to generate synthetic weather time-series is a correlated auto regression model, which follows the approach taken by (Dinwoodie and McMillan, 2013). Synthetic weather series are time series of weather conditions generated from statistical analysis of historical weather data sets.…”
Section: Previous Research Coupling Des With Metocean Modelsmentioning
confidence: 99%